PENGARUH VIDEO ANIMASI DALAM PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII DI SMP TMI ROUDHOTUL QUR’AN KOTA METRO - Siti Nur Kholifah; Triana Asih; Ratini Ratini (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
This research was conducted at TMI Roudhotul Qur'an Middle School located on Jl Pratama Praja Mulyojati 16b West Metro District, Metro City, Lampung Province. The purpose of this study was to determine the effect of animated videos in Problem Based Learning (PBL) learning on the critical thinking skills of class VIII students at TMI Roudhotul Qur'an Middle School Metro City. The type of research used in this research is a quantitative quasi-experimental (quasi-experimental research). The population used by all students of class VIII includes 7 (seven) classes with a total of 206 students. The design used is Post-test Only Control Design Non-equivalent Control Group Design with Cluster Random Sampling sampling technique. The sample of this research is class VIII B (control class) and VIII E (experimental class). Average post-test is 77.80 so that the increase is 13.50. Furthermore, based on the t-test, the tcount value was 2.172. The value of t table with df 55 at a significant level of 5% is 2.015. Therefore, tcount > ttable (2.172 > 2.004) and the significance value is smaller than 0.05 (0.000 <0.05) so that it can be stated that there is a significant increase in student learning outcomes scores in the experimental group or those given the Problem Based Learning model accompanied by Animation Videos. From these data, it can be seen that there is a significant increase in the average value of students' critical thinking skills.